Impact of a biofouling layer on the vapor pressure driving force and performance of a membrane distillation process - Goh, Shuwen (2013)
The heat and mass transfer resistances of fouling layers can cause a significant flux decline in a membrane distillation (MD) process. In addition, the hydrophilicity and microporous nature of a fouling layer can affect the driving force and correspondingly the flux in MD via curvature effects on the vapor pressure as described by the Kelvin equation. This study explores the effect of the hydrophilicity of the sludge on the particle size, vapor pressure and pore-size distribution (PSD) in the biofouling layer and on the permeation flux in cross-flow MD. Two sets of hydrophilic sludge cultures were selected via the Microbial-Adhesion-to-Hydrocarbon method. Cross-flow MD experiments conducted with these two sludges displayed a 60% reduction in the flux relative to using a Milli-Q water feed. However, there was no significant difference in the fluxes for the two sludges. Characterization of the pore-size distribution of the two sludges using evapoporometry, a novel technique based on the vapor-pressure depression caused by small pores, indicated a vapor-pressure depression of 31% and 21% for the more- and less-hydrophilic sludges, respectively. However the effect of the 10% difference in vapor-pressure depression, when combined with the effect of the biofouling layer on the heat- and mass-transfer resistances, could not be detected within the experimental error in this study. Nevertheless, a major conclusion is that the vapor-pressure depression caused by a biofouling layer, or other foulants, could cause a significant reduction in the driving force for MD.